2016
DOI: 10.1016/j.joto.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

After cochlear implantation: Complications related to flap around implants

Abstract: ObjectiveTo report complications related to flap around implants after cochlear implantation, possible causes of such complications and treatments.Methods and materialWe performed a retrospective analysis of children in whom complications related to flap around implants occurred after undergoing cochlear implantation in our department from 2005 to 2016.ResultsComplications among 1500 cochlear implantation (CI) recipients by the same surgeon included hematoma (n = 20) and seroma around implants (n = 15), of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…However, the outcome of revision surgery was not guaranteed. After unsuccessful revision surgery, two patients (40%, 2/5) developed skin necrosis with implant exposure, similar to previous reports [ 1 , 6 ]. Conservative treatment with foreign body retention would have aggravated the patient’s condition.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the outcome of revision surgery was not guaranteed. After unsuccessful revision surgery, two patients (40%, 2/5) developed skin necrosis with implant exposure, similar to previous reports [ 1 , 6 ]. Conservative treatment with foreign body retention would have aggravated the patient’s condition.…”
Section: Discussionsupporting
confidence: 90%
“…[ 3 ] Qin et al reported 15 seromas around implants, all of which occurred within 1–2 years after CI surgery, while Low reported that hematoma episodes occurred 2–12 years (median, 6 years) after CI. [ 6 , 7 ] Table 2 shows the onset times for each patient in our study population; the times ranged from 2 months at the earliest to 10 years at the latest with a mean of 31.4 months. Therefore, rigorous follow-up for flap complications should be performed for a long time after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination with pneumococcal conjugate vaccine (PCV13) and Haemophilus influenzae type B (Hib) should be given prior to implantation, especially in cases of inner ear anomalies with the aim of reducing the incidence of meningitis. We had no cases of meningitis during the current study; however, as all the children had been vaccinated against Streptococcus pneumoniae as well as Haemophilus influenzae type B, and had been given perioperative injectable cefuroxime 25…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative infection is one of the most common complications 5 , 7 , following cochlear implantation, and conservative treatments are suggested to be primary and first-line treatment. For post-CI infection, a routine procedure may sequentially involve antibiotic treatments, pus puncture, revision surgery and re-implantation 8 , which does not take into account the specific clinical postoperative manifestations of CI and may cause refractory SFI.…”
Section: Discussionmentioning
confidence: 99%